اللعب التعليمي ودوره في تعليم اللغة - بوراس, سليمان (جامعة الوادي - University of Eloued, 2023)
ملخص : يعد اللعب واحدا من المطالب الأساسية النفسية للطفل، يرتاح حين يمارسه، ويتفاعل مع بني جنسه حين يتواجد فيه، وهو مما يمكن أن يشكل شخصية الطفل في مكوناتها الحسية والحركية والانفعالية والعقلية ، وهذا هو ما جعل الأمم على مر التاريخ تهتم به، وتجعله مجالا لدراساتها من خلال تحديده وبيان شروطه التي يقوم عليها . وتأتي هذه المقالة لتبين هذه الجوانب المطروحة وتعطي القيمة الحقيقية لفاعلية اللعب في العمل التعليمي التعلمي . Abstract : Play is one of the basic psychological demands of the child, he relaxes when he practices it, and interacts with his gender when he is present in it, which can form the child's personality in its sensory, motor, emotional and mental components, and this is what has made nations throughout history interested in him, and make him a field for their studies by identifying him and indicating his underlying conditions . This article comes to show these aspects posed and gives the true value of the effectiveness of play in teaching -learning work.
مقال
Keywords: اللعب ; اللعب التعليمي ; الطفل ; وظائف اللعب